Exploring the frontiers of research co-production: the Integrated Knowledge Translation Research Network concept papers - Ian D. Graham; Chris McCutcheon; Anita Kothari (BMC, 2019)
Abstract Research co-production is about doing research with those who use it. This approach to research has been receiving increasing attention from research funders, academic institutions, researchers and even the public as a means of optimising the relevance, usefulness, usability and use of research findings, which together, the argument goes, produces greater and more timely impact. The papers in this cross BMC journal collection raise issues about research co-production that, to date, have not been fully considered and suggest areas for future research for advancing the science and practice of research co-production. These papers address some gaps in the literature, make connections between subfields and provide varied perspectives from researchers and knowledge users.